Sedentary Behavior Is Associated With Low Leisure-Time Physical Activity and High Body Fatness in Older Brazilian Adults - Sebastiao, Emerson; Bobitt, Julie; Papini, Camila Bosquiero; Nakamura, Priscila Missaki [UNESP]; Kokubun, Eduardo [UNESP]; Gobbi, Sebastiao [UNESP] (Sage Publications Inc, 2021)
Sedentary behavior (SB) has emerged as a new health risk factor, including risk of premature death. This study examined the association between SB and measures of physical activity and body fatness in older Brazilian adults. Self-report measures of SB (ie, sitting time [ST]), leisure-time physical activity (LTPA), and body fatness (body mass index [BMI]) were collected from 355 older adults aged 60 years and older by trained interviewers. Statistical procedures were conducted using SPSS software with significance set at P < .05. Overall, the median ST was 3 hours per day. Mean values of LTPA and BMI for the entire sample were 90.0 (197.4) min/week and 26.5 (4.9) kg/m(2), respectively. Partial correlations controlling for age revealed that ST was negatively associated with LTPA (pr = -.15 [-.25; -.04]; P = .006) and positively associated with BMI (pr = .25 [.14; .35]; P < .001). Age, BMI, and LTPA emerged as independent predictors of ST, explaining a small but significant variance in ST (R-2 = .12; P = .02). Furthermore, t test revealed a significant difference in LTPA and BMI between groups of different amounts of sitting. The findings suggest that prolonged ST may have a negative impact on LTPA and BMI in older Brazilian adults.
Keywords: body fat; chronic diseases; elderly; developing country; sitting time